Ankle Syndesmosis: A Qualitative and Quantitative Anatomic Analysis. (January 2015) - Williams, Brady T.; Ahrberg, Annette B.; Goldsmith, Mary T.; Campbell, Kevin J.; Shirley, Lauren; Wijdicks, Coen A.; LaPrade, Robert F.; Clanton, Thomas O.
Background: Syndesmosis sprains can contribute to chronic pain and instability, which are often indications for surgical intervention. The literature lacks sufficient objective data detailing the complex anatomy and localized osseous landmarks essential for current surgical techniques. Purpose: To qualitatively and quantitatively analyze the anatomy of the 3 syndesmotic ligaments with respect to surgically identifiable bony landmarks. Study Design: Descriptive laboratory study. Methods: Sixteen ankle specimens were dissected to identify the anterior inferior tibiofibular ligament (AITFL), posterior inferior tibiofibular ligament (PITFL), interosseous tibiofibular ligament (ITFL), and bony anatomy. Ligament lengths, footprints, and orientations were measured in reference to bony landmarks by use of an anatomically based coordinate system and a 3-dimensional coordinate measuring device. Results: The syndesmotic ligaments were identified in all specimens. The pyramidal-shaped ITFL was the broadest, originating from the distal interosseous membrane expansion, extending distally, and terminating 9.3 mm (95% CI, 8.3-10.2 mm) proximal to the central plafond. The tibial cartilage extended 3.6 mm (95% CI, 2.8-4.4 mm) above the plafond, a subset of which articulated directly with the fibular cartilage located 5.2 mm (95% CI, 4.6-5.8 mm) posterior to the anterolateral corner of the tibial plafond. The primary AITFL band(s) originated from the tibia 9.3 mm (95% CI, 8.6-10.0 mm) superior and medial to the anterolateral corner of the tibial plafond and inserted on the fibula 30.5 mm (95% CI, 28.5-32.4 mm) proximal and anterior to the inferior tip of the lateral malleolus. Superficial fibers of the PITFL originated along the distolateral border of the posterolateral tubercle of the tibia 8.0 mm (95% CI, 7.5-8.4 mm) proximal and medial to the posterolateral corner of the plafond and inserted along the medial border of the peroneal groove 26.3 mm (95% CI, 24.5-28.1 mm) superior and posterior to the inferior tip of the lateral malleolus. Conclusion: The qualitative and quantitative anatomy of the syndesmotic ligaments was reproducibly described and defined with respect to surgically identifiable bony prominences. Clinical Relevance: Data regarding anatomic attachment sites and distances to bony prominences can optimize current surgical fixation techniques, improve anatomic restoration, and reduce the risk of iatrogenic injury from malreduction or misplaced implants. Quantitative data also provide the consistency required for the development of anatomic reconstructions.